Association of ACE2 Polymorphisms and Derived Haplotypes With Obesity and Hyperlipidemia in Female Spanish Adolescents - Lumpuy-Castillo, Jairo; Vales-Villamarín, Claudia; Mahíllo-Fernández, Ignacio; Pérez-Nadador, Iris; Soriano-Guillén, Leandro; Lorenzo, Oscar; Garcés, Carmen (Frontiers in Cardiovascular Medicine, 2022)
Background: In the cardiovascular (CV) system, overactivation of the angiotensin converting enzyme (ACE) may trigger deleterious responses derived from angiotensin (Ang)-II, which can be attenuated by stimulation of ACE2 and subsequent Ang-(1-7) metabolite. However, ACE2 exhibits a high degree of genetic polymorphism that may affect its structure and stability, interfering with these cardioprotective actions. The aim of this study was to analyse the relationship of ACE2 polymorphisms with cardiovascular risk factors in children. Methodology: Five ACE2-single nucleotide polymorphisms (SNP), rs4646188, rs2158083, rs233575, rs879922, and rs2074192, previously related to CV risk factors, were analyzed in a representative sample of 12-to 16-year-old children and tested for their potential association with anthropometric parameters, insulin levels and the lipid profile. Results: Girls (n=461) exhibited lower rates of overweight, obesity, blood pressure, and glycemia than boys (n=412), though increased plasma lipids. The triglycerides (TG)/HDL-C ratio was, however, lower in females. Interestingly, only in girls, the occurrence of overweight/obesity was associated with the SNPs rs879922 [OR 1.67 (1.02-2.75)], rs233575 [OR 1.98 (1.21- 3.22)] and rs2158083 [OR 1.67 (1.04-2.68)]. Also, TG levels were linked to the rs879922, rs233575, and rs2158083 SNPs, and the TG/HDL-C ratio was associated with rs879922 and rs233575. Levels of TC and LDL-C were associated with rs2074192 and rs2158083. Furthermore, the established cut-off level for TG ≥ 90 mg/dl was related to rs879922 [OR 1.78 (1.06-2.96)], rs2158083 [OR 1.75 (1.08-2.82)], and rs233575 [OR 1.62 (1.00 -2.61)]. The cut-off level for TC ≥ 170 mg/dl was associated with rs2074192 [OR 1.54 (1.04-2.28) and rs2158083 [OR 1.53 (1.04-2.25)]. Additionally, the haplotype (C-G-C) derived from rs879922-rs2158083-rs233575 was related to higher prevalence of overweight/obesity and TG elevation. Conclusion: The expression and activity of ACE2 may be essential for CV homeostasis. Interestingly, the ACE2-SNPs rs879922, rs233575, rs2158083 and rs2074192, and the haplotype (C-G-C) of the three former could induce vulnerability to obesity and hyperlipidemia in women. Thus, these SNPs might be used as predictive biomarkers for CV diseases and as molecular targets for CV therapy.